2013
DOI: 10.1105/tpc.113.117697
|View full text |Cite
|
Sign up to set email alerts
|

SND1 Transcription Factor-Directed Quantitative Functional Hierarchical Genetic Regulatory Network in Wood Formation in Populus trichocarpa

Abstract: Wood is an essential renewable raw material for industrial products and energy. However, knowledge of the genetic regulation of wood formation is limited. We developed a genome-wide high-throughput system for the discovery and validation of specific transcription factor (TF)-directed hierarchical gene regulatory networks (hGRNs) in wood formation. This system depends on a new robust procedure for isolation and transfection of Populus trichocarpa stem differentiating xylem protoplasts. We overexpressed Secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
165
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(169 citation statements)
references
References 91 publications
(144 reference statements)
2
165
1
1
Order By: Relevance
“…PgNAC‐7 and these three MYBs were proposed by Duval et al . (2014) to form a regulatory network similar to the SND1 network defined in Arabidopsis (Zhong et al ., 2006) that is conserved in poplar (Lin et al ., 2013; Wang et al ., 2014). The regulation of lignin biosynthesis by members of the conserved SND1 transcriptional network has been well documented in conifer trees (Patzlaff et al ., 2003a,b; Bomal et al ., 2008, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…PgNAC‐7 and these three MYBs were proposed by Duval et al . (2014) to form a regulatory network similar to the SND1 network defined in Arabidopsis (Zhong et al ., 2006) that is conserved in poplar (Lin et al ., 2013; Wang et al ., 2014). The regulation of lignin biosynthesis by members of the conserved SND1 transcriptional network has been well documented in conifer trees (Patzlaff et al ., 2003a,b; Bomal et al ., 2008, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…PtrAldOMT2 has the most abundant monolignol biosynthetic gene transcript in stem-differentiating xylem (SDX) of P. trichocarpa and is the third highest transcribed gene in the whole SDX transcriptome (7). PtrAldOMT2 protein abundance is also the highest of all monolignol biosynthetic enzymes and accounts for 5.9% of the SDX proteome (22).…”
Section: Significancementioning
confidence: 99%
“…An expression vector containing a cauliflower mosaic virus 35S promoter and the PtrAldOMT2 gene fused at its C terminus with an sGFP coding sequence was overexpressed in P. trichocarpa SDX protoplasts, using our protocol (7,29). The transformed SDX protoplasts exhibited uniform green fluorescence consistent with the expression of a cytosolic enzyme (Fig.…”
Section: Ptraldomt2 Is a Homodimeric Cytosolic Enzyme Expressed Morementioning
confidence: 99%
See 1 more Smart Citation
“…We explored whether 110 direct targets of the four SND1-clade genes were coexpression neighbors in our network, including 76 genes identified as targets using transactivation assays and chromatin immunoprecipitation (ChIP) in protoplast-derived xylary tissue with a low degree of differentiation (Lin et al, 2013) and 34 genes (hereafter, non-ChIP targets) identified as transactivation targets based on different lines of experimental evidence (Ye and Zhong, 2015) (see Supplemental Data Set 9 for all target genes). Seventy-six of these 110 putative direct targets of (Potri.001G248700 and Potri.016G112100), LAC11 (Potri.004G156400), and LAC17 (Potri.001G184300, Potri.001G401300, and Potri.006G087100).…”
Section: Transcriptional Regulators Of Wood Developmentmentioning
confidence: 99%